Performance Analysis of Exponential Increase Exponential Decrease Back-Off Algorithm - Chunxuan Ye; Yan Li; Reznik, Alex (2010 IEEE Global Telecommunications Conference GLOBECOM 2010, 2010)
Since the IEEE 802.11 DCF adopted the Binary Exponential Back-off (BEB) algorithm in its contention window adjustment scheme, many alternative back-off algorithms were proposed in order to enhance the performance. Among them is an Exponential Increase Exponential Decrease (EIED) back-off algorithm, whose performance was simulated and analyzed in a special case of doubling or halving the contention window size. This paper provides an analytical analysis for the general EIED algorithm. A closed form saturation throughput and a closed form saturation delay are derived. Our analytical results further establish the performance improvement of the general EIED algorithm over the BEB algorithm and the basic EIED algorithm.